Deteksi Dini Golongan Darah Anak Panti Asuhan Mentawai Untuk Kesiapsiagaan Medis - Yoantrista, Nabilla; Yuniarti, Elsa (Penerbit Widina, Widina Media Utama, 2025)
Knowledge of blood type is essential for personal identification and plays an important role in various medical needs, including blood transfusion, blood donation, and emergency care. This community service activity aimed to improve health literacy and medical preparedness among children at the H. Syafri Moesa Mentawai Orphanage through ABO blood type screening. A total of 60 children participated in the screening, which was conducted using Anti-A and Anti-B reagents with the slide agglutination method. The results showed a distribution of blood types A (36.5%), B (17.5%), AB (17.5%), and O (28.6%), providing baseline data that had not previously existed at the orphanage. The activity demonstrated increased understanding among participants regarding the importance of knowing their blood type, and it produced a specific output in the form of a blood type database that can support health administration and emergency medical response. Overall, this program had a positive impact by enhancing medical preparedness and strengthening the orphanage’s capacity to manage the health identity data of its children.ABSTRAKPengetahuan tentang golongan darah merupakan informasi dasar yang penting sebagai identitas diri serta sangat dibutuhkan dalam pelayanan medis, seperti transfusi darah, donor darah, dan penanganan kedaruratan. Kegiatan ini bertujuan untuk meningkatkan pemahaman dan kesiapsiagaan medis anak-anak di Panti Asuhan Mentawai H. Syafri Moesa melalui pemeriksaan golongan darah sistem ABO. Pemeriksaan dilakukan pada 60 anak menggunakan reagen Anti-A dan Anti-B dengan metode slide aglutinasi. Hasil pemeriksaan menunjukkan distribusi golongan darah A (36,5%), B (17,5%), AB (17,5%), dan O (28,6%), yang sekaligus menyediakan data dasar golongan darah yang sebelumnya belum tersedia di panti. Kegiatan ini terbukti meningkatkan literasi kesehatan peserta mengenai pentingnya mengetahui golongan darah sejak dini, serta menghasilkan luaran spesifik berupa database golongan darah anak-anak panti yang dapat digunakan untuk administrasi kesehatan dan penanganan medis darurat. Secara keseluruhan, kegiatan ini memberikan dampak positif dalam meningkatkan kesiapsiagaan medis dan mendukung kemandirian pengelola panti dalam mengelola identitas kesehatan anak asuh.